The Production Unit of the State Vocational High School 1 Warungasem the Department of Motorcycle Engineering and Business (Universitas Negeri Semarang, 2021)
Production unit plays an important role in education of vocational schools but unfortunately not all vocational schools can manage it effectively. The problems faced by the production unit at vocational school in implementing its program are inadequate infrastructure, very minimal human resources managing the program, lack of school principal’s commitment, and lack of cooperation between the schools and industry. This study is limited to the management problem faced by the Production Unit of State Vocational High School 1 Warungasem, the study program of Motorcycle Engineering and Business. This includes HR management aspects, customer service, marketing strategies, and financial management. This study is quantitative research which aims to describe the management of the Motorcycle Engineering and Business Production Unit of the State Vocational High School 1 Warungasem. The respondents in this study were the school leaders, the Production Unit managers, teachers, and students. The data collection used questionnaires, observations, and interviews. Then they were analyzed using quantitative descriptive data. The results of the questionnaire assessment showed an average score of 44.4 or 84.2% for the aspect of HR management and an average score of 79.4 or 83.6% for the aspect of Customer Service. It means that both aspects are very good. Meanwhile, the Marketing Strategy obtained an average score of 15.3 or 76.5% which means it is good and the aspect of financial management obtained quite good result with an average score of 20 or 66.7%.